(untitled) (Bangladesh Pharmaceutical Journal, 2015)
An in vitro thrombolytic model was used to check the clot lysis effect of two herbal extracts viz., Desmodium paniculatum (L.) and Sarchochlamys pulcherrima (Roxb.) by using Streptokinase as positive control and water as negative control. D. paniculatum and S. pulcherrima showed 31.92 ± 8.09% and 36.12 ± 6.81% clot lysis, respectively. From our study we found that D. paniculatum and S. pulcherrima showed significant % of clot lysis effect with reference to Streptokinase (72.54 ± 6.03%). and water (3.48 ± 0.84%). DOI: http://dx.doi.org/10.3329/bpj.v17i1.22318 Bangladesh Pharmaceutical Journal 17(1): 67-69, 2014